Inferior Oblique Recession with 5 mm Loop to Correct Vertical Deviation and Inferior Oblique Overaction Secondary to Superior Oblique Palsy. Issue 3 (3rd July 2021) - Godts, D. J. M.; Deboutte, I. V. A.; Prinsen, S.; De Veuster, I.; Mathysen, D. G. P.
ABSTRACT: Purpose : To evaluate the effect of augmented inferior oblique recession (recession +5 mm loop) on the vertical deviation in primary position (PP) and the inferior oblique overaction (IOOA) in patients with unilateral congenital or acquired superior oblique palsy. Patients and methods : The medical records of patients who underwent unilateral inferior oblique recession with 5 mm loop during 2012 and 2019 were retrospectively reviewed. All patients had small to moderate manifest or intermittent hypertropia in PP and overaction of the inferior oblique muscle of +2 or +3 in lateral gaze. Patients who had combined inferior rectus surgery of the contralateral eye or who had previous vertical muscle surgery were excluded. Results : A total of 26 patients were included. Of these, three patients had combined horizontal muscle surgery. In 22 patients, the superior oblique palsy was congenital or longstanding, in 4 it was acquired and stable for more than 9 months. The mean preoperative vertical deviation in PP at distance and near was 14.7Δ and 11.2Δ, respectively. The mean postoperative vertical deviation was 5.7Δ and 4.1Δ after a mean follow-up of 19 months. The IOOA improved in all patients, 16 patients had an improvement of +2 and 10 patients had an improvement of +1. Conclusion : Inferior oblique recession with a 5 mm loop is a simple and quick technique to correct small to moderate hypertropia in primary position and inferior oblique overaction in contralateral gaze in patients with congenital, longstanding or acquired superior oblique palsy without risk of overcorrection.